Characterization and technological evaluation of coagulase-negative Staphylococci isolated from Sjenica sheep's ham - Žugić-Petrović Tanja; Marković Katarina G.; Grujović Mirjana Ž. (Kragujevac Journal of Science)
This study investigates the community of coagulase-negative staphylococci (CNS) in samples of Sjenica sheep's ham from different villages across three seasons over a 120-day maturation period. The CNS group was identified into five distinct species: Staphylococcus epidermidis, S. saprophyticus, S. carnosus, S. xylosus, and S. equorum. The safety evaluation revealed no hemolytic activity in any tested isolates, while resistance to novobiocin was observed in S. xylosus and S. saprophyticus isolates. The technological properties of the isolated CNS were assessed, including tolerance to different temperatures, pH values, salt concentrations, as well as proteolytic and lipolytic activity. Results demonstrated the ability of all tested isolates to grow across various pH values and salt concentrations, with isolates of S. carnosus and S. epidermidis showing tolerance to 45°C. The best technological properties were shown by S. carnosus, followed by S. equorum. These findings provide insights into the potential applications of CNS in food processing industries, as putative starters.